Induction of defense-related biochemical changes by elicitors of red rot pathogen and a non-pathogen in sugarcane cell culture - P. VIDHYASEKARAN, A. RAMESHSUNDAR and (Indian Phytopathology, 2003)
A glycoprotein elicitor isolated from the mycelial cell wall of the red rot pathogen C. fa/catum was used to detect the possible induction of HP2’ 02’, lipoxygenase, lipid peroxidation, SOD and catalase in cell suspension cultures of sugarcane. A rapid outburst and a spurt in the generation of active oxygen species especially H 202 was observed indicating an early molecular event in recognition of the pathogen by the host cells. Significant induction of lipid breakdown products due to elicitor treatment has also been recorded in the suspension-cultured cells of sugarcane. However, higher levels of the suppressor enzymes viz., catalase and superoxide dismutase were found to be maintained throughout in the cells of sugarcane suspension cultures without any elicitor treatment.